Demonstrating the presence of Ehrlichia canis DNA from different tissues of dogs with suspected subclinical ehrlichiosis - Rodríguez-Alarcón, Carlos Arturo (2020)
Background: Nowadays, Ehrlichia canis receives increasing attention because of its great morbidity and mortality in animals. Dogs in the subclinical and chronic phases can be asymptomatic, and serological tests show cross‑reactivity and fail to differentiate between current and past infections. Moreover, there could be low parasitaemia, and E. canis might be found only in target organs, hence causing results to be negative by polymerase chain reaction (PCR) on blood samples.Methods: We evaluated by PCR the prevalence of E. canis in blood, liver, spleen, lymph node and bone marrow sam‑ples of 59 recently euthanised dogs that had ticks but were clinically healthy.Results: In total, 52.55% of the blood PCRs for E. canis were negative, yet 61.30% yielded positive results from tissue biopsies and were as follows: 63.15% from bone marrow; 52.63% from liver; 47.36% from spleen; and 15.78% from lymph node. In addition, 33% had infection in three tissues (spleen, liver and bone marrow).Conclusions: Our results show the prevalence of E. canis from tissues of dogs that were negative by blood PCR. Ehrli-chia canis DNA in tissue was 30% lower in dogs that tested negative in PCR of blood samples compared to those that were positive. However, it must be taken into account that some dogs with negative results were positive for E. canis in other tissues.Keywords: Ehrlichia canis, Biopsies, Spleen, Bone marrow, Liver, Lymph node